Botanical composition of yearling-steer and mature-ewe diets in the Kansas Flint Hills - Sowers, Consuelo Ann (Kansas State University, 2018)
Eight native tallgrass pastures infested with sericea lespedeza (initial basal frequency = 2.9 ± 2.74%) were grazed by yearling beef steers (n = 279 / yr; 1.1 ha / steer) from 15 April to 15 July for 2 grazing seasons. Subsequent to steer grazing, mature ewes (n = 813 / yr) were allowed to graze 4 of the 8 pastures (0.15 ha / ewe) from 31 July to 1 October. Remaining pastures were rested until the subsequent April. Animals were allocated randomly to pastures annually; grazing treatments remained fixed for the 2-yr experiment. Four permanent 100-m transects were laid out in a north-south gradient in each pasture. Beginning 1 May, steer diet composition was monitored by collecting 5 fresh fecal pats along each transect at 2-wk intervals until steers were removed on 15 July. Fecal pats were dried and ground individually and then composited by weight within transect. Twenty-five mature ewes from each pasture were randomly selected to monitor diet composition. On 15 August and 15 September, ewes were gathered and restrained; fecal grab samples were then collected from the individuals selected for diet composition analysis. Microhistological analysis was conducted on steer fecal composites and fecal samples from individual ewes, using pure samples of 17 predominant grass, forb, and browse species from the experimental site as reference standards. Fecal and standard samples were prepared for microhistological analysis and viewed using a compound microscope at 100x magnification. Botanical composition of pastures was measured in October and compared with botanical composition of yearling beef steer and mature ewe diets. Diet selection exercised by yearling steer and mature ewes was evaluated using Kulcyznski’s Similarity Index. Proportions of bare soil, litter cover, and total basal vegetation cover did not differ (P ≥ 0.38) between pastures for either steer or sheep diet evaluations. Similarly, basal cover of the 17 plants selected as microhistological standards did not differ (P ≥ 0.07) between pastures for either steer or sheep diet evaluations. The proportions of total graminoids and total forbs and forb-like plants in the diets of grazing steers were not different (P = 0.37) between sampling periods and were interpreted to indicate steer diets were strongly dominated by graminoids (≥ 88.4% of diets). Yearling beef steers consistently exhibited strong preference (i.e., ≤ 6% similarity with pasture composition) for Bouteloua gracilis, Bouteloua dactyloides, Dalea purpurea, and Liatris punctata, whereas they strongly avoided Lespedeza cuneata and Symphyotrichum ericoides. The proportions of total graminoids and total forbs and forb-like plants in the diets of grazing ewes were not different (P = 0.67) between sampling periods and were interpreted to indicate that mature ewes selected consistent proportions of grasses and forbs over time (average = 58 and 42% of diets for grasses and forbs, respectively). Mature ewes consistently exhibited strong preference (i.e., ≤ 10% similarity with pasture composition) for Bouteloua gracilis, Bouteloua dactyloides, Dalea purpurea, Liatris punctata, Vernonia baldwinii, and Ambrosia artemisiifolia. None of the 17 microhistological reference standards were consistently avoided by ewes.
Keywords: Botanical composition; Microhistological analysis; Steer; Sheep; Lespedeza cuneata